Cone Dystrophy in Patient with Homozygous RP1L1 Mutation. (29th January 2015) - Kikuchi, Sachiko; Kameya, Shuhei; Gocho, Kiyoko; El Shamieh, Said; Akeo, Keiichiro; Sugawara, Yuko; Yamaki, Kunihiko; Zeitz, Christina; Audo, Isabelle; Takahashi, Hiroshi
Abstract : The purpose of this study was to determine whether an autosomal recessive cone dystrophy was caused by a homozygous RP1L1 mutation. A family including one subject affected with cone dystrophy and four unaffected members without evidence of consanguinity underwent detailed ophthalmic evaluations. The ellipsoid and interdigitation zones on the spectral-domain optical coherence tomography images were disorganized in the proband. The proband had a reduced amplitude of cone and flicker full-field electroretinograms (ERGs). Focal macular ERGs and multifocal ERGs were severely reduced in the proband. A homozygous RP1L1 mutation (c.3628T>C, p.S1210P) was identified in the proband. Family members who were heterozygous for the p.S1210P mutation had normal visual acuity and normal results of clinical evaluations. To investigate other putative pathogenic variant(s), a next-generation sequencing (NGS) approach was applied to the proband. NGS identified missense changes in the heterozygous state of the PCDH15, RPGRIP1, and GPR98 genes. None of these variants cosegregated with the phenotype and were predicted to be benign reinforcing the putative pathogenicity of the RP1L1 homozygous mutation. The AO images showed a severe reduction of the cone density in the proband. Our findings indicate that a homozygous p.S1210P exchange in the RP1L1 gene can cause cone dystrophy.